OPTIMALISASI JOB PERFORMANCE OPERATOR BAGIAN TWISTER MENGGUNAKAN METODE WORK SAMPLING DI PT XYZ - Maulana, Moch Ilan; Perwiranegara, Agus Alamsyah (Universitas Majalengka, 2021)
Labor is an important resource besides raw materials, capital, methods and machines. The quality and quantity of labor must be in accordance with the needs of the company, effective and efficient efforts to support the achievement of goals. PT XYZ, the Twister division, still uses human assistance. If one of the operators is not working properly, such as playing on the cellphone while working, sitting around for too long while working, it will affect the target of completing production. PT XYZ requires measurement of working time to determine the standard time and the level of productivity produced by the Twister operator. To solve the problems faced, a work sampling method will be used. The work sampling method is a work measurement with observations to assess the work activities of machines or labor. From visiting hours for 5 working hours per day, 3 days of visits or a total of 900 minutes are carried out, with observations of worker productivity and worker activities. obtained an average percentage of productive activities of 0.77. the number of productive minutes is 693 minutes, the number of units completed during the observation is 156 kg of yarn, the cycle time is 4.44 minutes, the normal time with the adjustment factor is 1.51 with a result of 6.7 minutes, and the standard time with a factor The allowance is 1.47 with a result of 9.85 minutes.